EDUKASI GIZI PASIEN POST OPERASI DI BANGSAL MAWAR RSUD DR. SOEHADI PRIJONEGORO SRAGEN - Discha Andriani; Nurul Kholifatul Hamidah; Elysa Rachmawati Pratiwi; Irma Mustika Sari; Ratna Indrayani (Jurnal Padamu Negeri, 2026)
Inadequate nutritional intake in post-operative patients can delay wound healing and increase the risk of complications such as wound dehiscence, infection, and fluid imbalance. Objective: This health education activity aimed to improve family understanding of proper post-operative nutrition and their ability to apply a balanced diet to support recovery. Methods: The activity involved post-operative patients and their families using lectures, demonstrations, and interactive discussions supported by leaflets. Results: Pre-test results showed that participants had a moderate level of knowledge regarding post-operative nutrition. After the educational intervention, post-test results demonstrated a significant improvement in participants’ knowledge. Conclusion: Health education on proper nutrition for post-operative patients was effective in significantly increasing participants’ knowledge and understanding of nutritional management during the recovery period.